Bone mineralization‐dependent craniosynostosis and craniofacial shape abnormalities in the mouse model of infantile hypophosphatasia. Issue 2 (28th December 2015) - Durussel, John; Liu, Jin; Campbell, Cassandra; Nam, Hwa K.; Hatch, Nan E.
Abstract : Background: Inactivating mutations in tissue‐nonspecific alkaline phosphatase (TNAP) cause hypophosphatasia (HPP), which is commonly characterized by decreased bone mineralization. Infants and mice with HPP can also develop craniosynostosis and craniofacial shape abnormalities, although the mechanism by which TNAP deficiency causes these craniofacial defects is not yet known. Manifestations of HPP are heterogeneous in severity, and evidence from the literature suggests that much of this variability is mutation dependent. Here, we performed a comprehensive analysis of craniosynostosis and craniofacial shape variation in the Alpl −/− mouse model of murine HPP as an initial step toward better understanding penetrance of the HPP craniofacial phenotype.Results: Despite similar deficiencies in alkaline phosphatase, Alpl −/− mice develop craniosynostosis and a brachycephalic/acrocephalic craniofacial shape of variable penetrance. Only those Alpl −/− mice with a severe bone hypomineralization defect develop craniosynostosis and an abnormal craniofacial shape.Conclusions: These results indicate that variability of the HPP phenotype is not entirely dependent upon the type of genetic mutation and level of residual alkaline phosphatase activity. Additionally, despite a severity continuum of the bone hypomineralization phenotype, craniofacial skeletal shape abnormalities and craniosynostosis occur only in the context of severely diminished bone mineralization in the Alpl −/− mouse model of HPP. Developmental Dynamics 245:175–182, 2016 . © 2015 Wiley Periodicals, Inc. Key Findings: Severity of hypophosphatasia is not entirely mutation dependent. Craniosynostosis and craniofacial shape abnormalities occur only in a subset of Alpl−/− mice. Craniosynostosis only occurs in the context of severely diminished bone mineralization in the Alpl−/− mouse model of hypophosphatasia.